TUNGAU PADA DAUN MANGGA (Mangifera Indica) - Rawati Panjaitan (FMIPA Universitas Papua, 2014)
Mites have hostplant specifications or host plants. Mites can be destructive and deadly of which is the host plants a mango crop. Mites on mango crops will cause the leaves yellow and fall off prematurely. This is will lead to the disruption of the productivity of mango. It is necessary for research to identify the mites that infect the mango crop. The method is carried out by direct observation. Mites were taken from the surface of mango leaves later in preservation with several levels of concentration of alcohol, and polyvinyl laktofenol. Then, observed under a microscope and documented for identification purposes. Mites on the leaf surface of manalagi mango (Mangifera indica) found two species, it is Oligonychus sp. and Oligonychus ilicis (Family: Tetranychidae, Superfamily: Tetranychoidea). Oligonychus sp. hallmark is rounded body shape like a spider, with a body is transparent and there are two long seta on posterior part. While Oligonychus ilicis has a characteristic elongated rounded body shape, red, and there is a short posterior seta. Oligonychus sp. and Oligonychus ilicis live as parasites on the surface of mango leaves that can lead to wrinkled leaves, yellow and to fall. Oligonychus life cycle starts from the eggs develop into Nympha and then adult.